(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Significant gains are predicted as a result of the study because the stabilisation of soil using industrial wastes has emerged as a serious issue in building engineering. The current experimental work provides a clear rationale for the acceptability of using the locally available Rice Husk Ash (RHA) in the construction industry in order to reduce the volume of waste that must be disposed of to the environment, causing environmental contamination. Because stabilising materials like cement and lime are becoming more expensive, popular ground restoration methods are becoming more expensive. By substituting RHA for a sizeable amount of the stabilising agent, the cost of stabilisation could be reduced. Risks to the environment will also be decreased. This study investigates the stability and compaction of stabilised soil.